Analisis Politik Hukum dalam Undang-Undang Penyelenggaraan Haji di Indonesia - Nida Rafiqa Izzati; Opia Tatarisanto; Mafaza Rohadatul Aisy; Luthfi Nur Azizah (Fakultas Hukum, Universitas Warmadewa, 2024)
Hajj is one of the obligations for every Muslim who is mature and capable of performing it. Therefore, regulations regarding the organization of Hajj in a region are intriguing to discuss. The purpose of this article is to identify the definition of legal politics and Hajj, inform the history of the development of regulations on Hajj organization in Indonesia, and analyze legal politics within these laws. This research employs a normative juridical research method using legislative approaches, conceptual approaches, and historical approaches. The findings of this article indicate that from a legal-political perspective, Law No. 13 of 2008 concerning the Implementation of Hajj and Law No. 34/2014 concerning Hajj Financial Management are considered to ensure legal certainty for prospective Hajj pilgrims. Despite concerns regarding Article 30 paragraph (1) of the law causing legal uncertainty due to the continued practice of KBIH (Hajj Organizing Agencies) charging additional fees, the government argues that according to Article 29 paragraphs (1) and (2), Hajj guidance should be provided without charge to pilgrims. The latest law addressing this issue is Law No. 8 of 2019, which states that Hajj is the fifth pillar of Islam mandatory for every capable Muslim, as also guaranteed in the 1945 Constitution. Improvements in the organization of Hajj and Umrah should not only focus on improving the quality of service to pilgrims but also address all aspects involved in the organization of Hajj and Umrah.